THERMAL BEHAVIOUR OF WEATHERED AND CONSOLIDATED MARBLES - Ruedrich J.; Weiss T.; Siegesmund S. (My University, 2002)
To optimise stone consolidation it is necessary to understand the mechanisms of weathering in marbles, the control by the mineralogical composition and the rock fabric. The knowledge of how the stone consolidants affect the weathering mechanisms and if they are compatible with the stone is also an important consideration. The weathering of marble can begin with thermal stress whereby cracks are generated. To verify whether consolidation influences the thermal behaviour of marbles, we compared the behaviour of weathered and consolidated marbles. For the investigations four marbles were selected with various fabrics (e.g. texture, grain size, grain boundary geometry, etc.) and different weathering conditions. Three consolidation approaches were adopted: a solved polymethyl-methacrylate (PMMA I) dissolved in xylenes, a polysilicic acid ester (PSAE) and a total impregnation with a monomer methyl-methacrylate (PMMA II). Measurements of the porosity and effective pore size distribution evidenced a strong modification of the pore space by consolidation. Both PMMA approaches show a reestablishment of cohesion which can be determined by ultrasonic velocity measurements. The most conspicuous change of thermal dilatation behaviour is a pronounced reduction of expansion for the PMMA II consolidated marbles. By reaching the glass transition temperatures of PMMA I and PMMA II, a pronounced residual strain is observed in thermal dilatation measurements. This does not necessarily coincide with a deterioration, since ultrasonic wave velocities do not show a drastic decrease in thermally treated consolidated marbles. The PSAE consolidated marbles only show minor changes of dilatation, but due to its low bonding effect no significant cohesion between the crystals occurs.